Are Conditional Sentence Orders Used Differently for Indigenous Offenders? A Comparison of Sentences and Outcomes in Canada - Gutierrez, Leticia (Canadian journal of criminology and criminal justice, 2020)
Conditional sentence orders (CSOs) were introduced in Canada in 1996, largely as a mechanism to address the overreliance on incarceration. This sentencing option is particularly relevant for Indigenous individuals who have been vastly overrepresented in custodial settings. Despite being in place for over twenty years, little is known about the use and effectiveness of CSOs. The current study examined the use and outcomes of CSOs for Indigenous (n = 749) and non-Indigenous offenders (n = 1,625) in one Canadian province. Specifically, the length of CSO, frequency and type of optional conditions, number of breaches, and rates of reoffending were compared between the two groups. Results from a logistic regression, controlling for risk relevant co-variates, indicated that Indigenous individuals tended to receive shorter CSOs compared to Caucasian individuals. However, Indigenous individuals were 35% more likely than Caucasian individuals to be convicted of a breach and more likely to incur multiple breaches while on a CSO. Despite the differences in the rates of breaches, the likelihood of reoffending over a two-year period was equivalent across the two groups. Although the reasons for breach were for the current study, future research should investigate this further to determine whether increased breach rates for Indigenous individuals are the result of more rule-violating behaviour, an inequity in the fairness of the conditions applied to Indigenous versus Caucasian individuals, or whether it is possible that breaches are over-detected and convicted at a higher rate for Indigenous individuals. Greater awareness of the underlying mechanisms related to increased breach rates affords the opportunity to ensure that CSOs are consistently implemented, something which will contribute to achieving the objective of successful diversion from imprisonment.